Expanding Homogeneous Culture of Human Primordial Germ Cell–Like Cells Maintaining Germline Features Without Serum or Feeder Layers. Issue 5 (May 2022) - Kobayashi, Mutsumi; Kobayashi, Misato; Odajima, Junko; Shioda, Keiko; Hwang, Young Sun; Sasaki, Kotaro; Chatterjee, Pranam; Kramme, Christian; Kohman, Richie E.; Church, George M.; Loehr, Amanda R.; Weiss, Robert S.; et al.
Abstract : (Abstracted from Stem Cell Rep 2022;17(3):507–521) Primordial germ cells (PGCs) are embryonic precursors of gametes that are extensively studied in research settings. Human primordial PGC–like cells (hPGCLCs) are a surrogate model for embryonic PGCs that present difficulties in in vitro cell culture and expansion due to rapid loss of PGC-like identity and limited cell survival.